The influence of process variables of preparation of oxycellulose beads on their dissolution profile - Bajerová, Martina; Muselík, Jan; Gajdziok, Jan; Masteiková, Ruta; Dvorácková, Katerina (Acta poloniae pharmaceutica, 2013)
Particles preparation from biodegradable polymers as carriers for the controlled release of drugs has been the focus of many investigations and the subject of a growing field of research in recent years. The aim of this study was to develop and optimize the preparation of oxycellulose beads containing diclofenac sodium as a model drug. Particle size, surface, drug content and encapsulation efficiency were evaluated, drug dissolution profiles were measured and drug release mechanism estimated. The prepared oxycellulose beads were uniform in size with encapsulation efficiency ranging from 53.2 to 74.9%. The lower temperature of the crosslinking solution and its saturation with diclofenac sodium increased the encapsulation efficiency, especially when both parameters were combined. The application of ultrasound had a negative effect on drug encapsulation. The dissolution of diclofenac sodium in pH 1.2 was close to zero as its solubility in this medium is very limited. The drug release in pH 6.8 lasted from 10 to 16 h showing biphasic behavior with a significant lag time. T1/2 decreased with increasing encapsulation efficiency and ultrasound application. Diclofenac sodium was released from the prepared oxycellulose particles by diffusion as well as by erosion process; ahigh correlation was found with zero order kinetics.
Keywords: methylcelulosa; chemie farmaceutická; diklofenak; rozpustnost; Delayed-Action Preparations; Temperature; difuze; Diffusion; Kinetics; ultrazvuk; Chemistry, Pharmaceutical; povrchové vlastnosti; velikost částic; Anti-Inflammatory Agents, Non-Steroidal; Technology, Pharmaceutical; teplota; Methylcellulose; Calcium Chloride; koncentrace vodíkových iontů; farmaceutická technologie; Surface Properties; léky s prodlouženým účinkem; antiflogistika nesteroidní; Solubility; Particle Size; Drug Carriers; kinetika; reagencia zkříženě vázaná; Hydrogen-Ion Concentration; chlorid vápenatý; Cross-Linking Reagents; nosiče léků; Diclofenac; Ultrasonics